Supplemental Data for "Survey of drug use and its association with herd-level and farm-level characteristics on German dairy farms" - Abdallah, Mies; Justus Liebig University Giessen (My University, 2023)
The data set contains supplementary tables for paper: "A". This is a voluntary survey of the use of medicines on 50 dairy cow farms in Germany for the year 2020. The tables contain information on the questionnaire used, the farm parameters surveyed, the classification of the regions, the groups of active substances identified, extended information on the statistical tests and the frequencies of the documented diagnoses.
Keywords: veterinary drugs; treatment frequency; substance monitoring; dairy farms; ddc:630